ANALISA PENGARUH PERUBAHAN BEBAN TERHADAP KINERJA MOTOR INDUKSI 3 FASA SCRAPER CONVEYORDI PT. CITRA SIWIT LESTARI - Sartika, Linda; prasetia, abdul muis; Nicholas, ishak Edison Nanda (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2023)
An organization or sector now needs to own a three-phase induction generator. The condition in which the factory was in operation forced the 3-phase scraper conveyor induction motor at PT Citra Sawit Lestari to continue to move the palm oil that is transported from the truck to the thresher. This process continues as long as the factory operates Under these conditions the load obtained by the 3-phase scraper conveyor induction motor affects the condition and performance of the induction motor This research was conducted on a 3-phase scraper conveyor induction motor using a quantitative approach that allowed the company to find out the causes of the reduced performance of 3-phase induction motors and find out the actions that must be taken so that the performance of 3-phase induction motors remains optimal Based on this research, it was concluded that changes in load could affect the performance of a 3-phase induction motor and the MAPE value of motor torque was 0.038%, motor power is 0.0008%, and rotational speed is 0.025%. With an average MAPE percentage value of less than 10%, this indicated that the performance of the 3-phase induction motor was still very good.